PROGRAM PEMBERDAYAAN LANSIA: MENINGKATKAN KESEHATAN, PENGETAHUAN, DAN KEMANDIRIAN DALAM MASYARAKAT - Hebert, Hocwin; Verrino Adityya; Ivander Destian Luis; Peter Reynard Susanto; Adrian Chandra; Hartati, Ery (Jurnal Pengabdian, 2025)
Rapid technological developments have changed the way we access information. In the past, search engines such as Google.com required users to select the right keywords and filter the results obtained. However, with the presence of artificial intelligence such as ChatGPT and Suno AI, interactions with technology have changed significantly. Users can now communicate naturally with AI, although understanding how it works and its limitations remains important. The purpose of this activity is to provide students of SMA Xaverius 3 Palembang with an understanding of the concept of AI and prompting techniques in Generative AI, so that they are able to use it wisely to support learning and creative exploration. This activity includes providing materials, AI demos, and evaluations with Quiziz. The results of the activity show that students not only understand the basic theory of AI, but are also able to apply prompting to various AI platforms such as ChatGPT, Microsoft Designer, and Suno AI.